Job Satisfaction Of Workers In Dramatic Montage In Syrian Drama Production Companies (Damascus University Journal of arts and humanities sciences, 2025)
This study was interested in identifying the job satisfaction of workers in dramatic montage in Syrian drama production companies, In order to achieve a number of objectives, centered on identifying the degree of job satisfaction, And knowing the extent to which each factor of job satisfaction affects the work of the editor, In addition to knowing the differences in job satisfaction between categories of demographic variables, To achieve this, the researcher relied on the use of the descriptive analytical method, and the questionnaire and in-depth interview tools, where the sample consisted of (20) editors who work in dramatic montage in Syrian drama production companies, They were selected through a comprehensive survey of the research community, and then the questionnaires were transcribed and analyzed using the statistical analysis program (SPSS). The study concluded a set of results explaining the impact of job satisfaction factors of workers in dramatic montage Syrian drama production companies, as follows:• The importance of their work and the burdens resulting from it do not satisfy them, and they need to increase management’s attention to their role, and reduce the burdens facing them.• Work relations with superiors and colleagues do not satisfy them, and they need to increase professional cooperation among employees in general, in• addition to the need for management to stay away from bias in treating its employees.• The salaries and bonuses are low compared to the effort expended in editing the series on the one hand, and the high prices on the other hand, and thus their dissatisfaction with them increases, and they are in great need for the management to reconsider the financial allocations and increase them quickly, in addition to raising the value of the bonuses for additional work, and not delaying the delivery the amounts owed to employees.• Professional security and stability are moderately satisfied, and are somewhat equivalent to their desires and ambitions.• The organizational structure of the production company is low, and therefore as the organizational structure of the company improves, the degree of satisfaction for employees increases.• Professional growth, career advancement and promotion are moderately satisfying.• The job performance of the employees no longer satisfies them because everything around them makes it work in a normal way, which requires drama production companies to adopt new methods that are comfortable for the employees.There are individual differences in the degree of  job satisfaction for workers in dramatic montage in Syrian drama production companies due to the influence of demographic variables as follows:• The largest portion belongs to private sector production companies at a rate of 75%, while the percentage of those affiliated with public sector production companies reached 25%.• The largest percentage of editing workers are male, at 90%, while only a small number of females, at 10%, and this relates to the specificity of the editing profession itself, such as being full-time, not adhering to a specific number of hours, and sometimes having to sleep in the company. Females have domestic and educational responsibilities that only allow them to work in an organized manner or The Independent.• The majority of age groups working in editing are between 30 and less than 45 years old, at a rate of 45%.• University degrees in terms of academic qualification reached 70%.• Long experience extending over 15 years prevailed by 45%.• The category of unmarried people was higher than married people, with the percentage of celibacy at 55%, while the percentage of married people was 45%, and this is related to the fact that the editing profession requires long preoccupations most of the time.
Keywords: Job satisfaction; Workers; Dramatic Montage; Production Companies; Syrian Drama